Investigation of Common Bacterial Pathogens Leading to Urinary Tract Infections among Patients with Diabetes Mellitus in Sub-Saharan Africa. - Nakkungu, Jackline (Student's Journal of Health Research Africa, 2021)
Background: The risk of diabetic patients acquiring UTIs is higher than that of their non-diabetic counterparts. This is due to the damage on the urinary bladder nerves caused by high blood glucose levels. This nerve damage reduces the ability of the urinary bladder to sense the presence of urine in it. As a result, urine stays for a long time in the bladder, increasing the growth of the bacteria in urine. UTI’s may lead to emphysematous pyelonephritis, cystitis in females, renal and perirenal abscess, papillary necrosis, xanthogranulomatous pyelonephritis, and fungal infections. There is limited knowledge about the bacteria affecting diabetic patients in Uganda. Methodology: In a cross-sectional study, 76 diabetic patients at Our Lady of Consolata Kisubi Hospital had their urine samples collected and analyzed for the presence of uro-bacterial pathogens in the microbiology laboratory at the University of Kisubi. Patients were instructed on how to collect midstream urine, which were cultured on blood agar and MacConkey agar plates. The bacteria were identified according to colony size, shape, and hemolysis. Several biochemical tests were used to confirm the presence of the different bacteria strains from the individual subcultured colonies Results Escherichia coli was the most predominant bacterium associated with UTIs in diabetes mellitus with an abundance of 42.3 %. This was followed by Klebsiella species with 21.1%, Staphylococcus aureus with 14.1%, Streptococcus species at 11.76%, Proteus species at 5.8%, Enterococcus faecalis at 3.5%, and Serratia marcescens with 1.17%. Female diabetic patients were found to be more infected with uropathogenic than their male diabetic counterparts. Conclusion and recommendations: Escherichia coli, Klebsiella species, Staphylococcus aureus, Streptococcus species, Proteus species, Serratia marcescens, and Enterococcus faecalis were identified to be commonly found in the urine of patients with diabetes mellitus. More screening and early management of such infections are needed in Sub-Saharan Africa.